Critical Study On The Manipulation Of The History Of Pancasila's Birth In The New Order Version - Ganjar Razuni (Universitas Sultan Ageng Tirtayasa, 2024)
The writing of the historical birth of Pancasila during the New Order was biased, starting with the stage of historical sources (heuristics). In this stage, the New Order did not use the main source or historical facts, namely, in this case, the original archive of the Minutes of the BPUPKI and PPKI sessions. Pancasila history writing during the New Order only used the 1945 Preparatory Manuscript of the Constitution book edited by Mr. Muhammad Yamin. However, the book is only a copy of the minutes of the BPUPK and PPKI sessions, not the original archive. Based on this source error, the writing of the history (historiography) of the birth of Pancasila was born, which places Mr. Yaminof as well as Mr. Soepomo as figures who participated in the creation of Pancasila, apart from Bung Karno. During the New Order, this historical construction was used to erase the commemoration of Pancasila Day every June 1. Currently, the alignment of the history of the birth of Pancasila has been carried out by Presidential Decree No. 24 of 2016 concerning the birth of Pancasila. However, the academic straightening of history needs to be done more seriously and deeply.